Persistent Hypercalcemia Crisis and Recurrent Acute Pancreatitis Due to Multiple Ectopic Parathyroid Carcinomas: Case Report and Literature Review of Mediastinal Parathyroid Carcinoma - Jiajue, Ruizhi; Song, An; Wang, Ou; Li, Wei (Frontiers in Endocrinology, 2020)
Mediastinal parathyroid carcinoma (PC) is a rare entity in primary hyperparathyroidism. The aim of this report is to demonstrate a case of mediastinal PC, and to provide a systemic literature review of this rare condition. A 34-year-old woman who had already undergone two cervical operations for hyperparathyroidism suffered from another recurrence, presenting with recurrent acute pancreatitis and persistent hypercalcemic crisis. Technetium-99 methoxyisobutylisonitrile imaging (MIBI) and computed tomography scanning (CT) identified three possible parathyroid tumors, one of which was the recurrence of residual tumor locating in the thyroid region, while the other two were ectopic tumors locating in the suprasternal fossa and thymus region, respectively. Pathological examination confirmed the diagnosis of PC. We conducted a systemic literature review by searching the PubMed MEDLINE from 1951 to 2019 for studies of all types in the English language only, using terms “mediastinal, mediastinum, parathyroid, carcinoma.” Including our reported case, a total of 21 cases with ectopic mediastinal PCs were assessed for demographic data, tumor location and size, biochemical findings, and symptomatology, etc. Two thirds of the patients were men, with a mean age of 44 years old, a mean serum calcium of 14.2 mg/dl, and a mean serum intact parathyroid hormone of 1,216 pg/ml. We identified 89.5% of carcinomas in the anterosuperior mediastinum, and 10.5% in the middle mediastinum, with a mean diameter of 54 mm, and a mean weight of 216 g. MIBI and CT were the most commonly used methods to localize these mediastinal tumors, with 69.2 and 100% sensitivity, respectively. Half of the patients underwent more than one operation. Diagnosis and treatment of mediastinal PCs represent a challenge. Early suspicion, appropriate preoperative localization studies, and the cooperation of endocrinologists and surgeons are crucial in the effective management.